2008
DOI: 10.1007/s10658-008-9340-z
|View full text |Cite
|
Sign up to set email alerts
|

BABA effects on the behaviour of potato cultivars infected by Phytophthora infestans and Fusarium solani

Abstract: Since most plants possess resistance mechanisms which can be induced upon pre-treatment with a variety of chemical compounds, the use of β-aminobutyric acid (BABA) as a defence inducer without reported toxic effect on the environment was studied. The aim of this work was to analyse the effectiveness of BABA to induce resistance against Phytophthora infestans and Fusarium solani in potato cultivars differing in their level of resistance to late blight. The behaviour of some components of biochemical mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…At this time, tubers were washed with distilled water, disinfected by immersion in 2.5 g l −1 sodium hypochlorite for 5 min and washed again with distilled water, and then used for phytopathological assays. Protection against P. infestans and F. solani was evaluated as described by Olivieri et al (2009). Briefly, for evaluation of P. infestans 20 tubers per treatment were used in five independent replicates.…”
Section: Phytopathological Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, tubers were washed with distilled water, disinfected by immersion in 2.5 g l −1 sodium hypochlorite for 5 min and washed again with distilled water, and then used for phytopathological assays. Protection against P. infestans and F. solani was evaluated as described by Olivieri et al (2009). Briefly, for evaluation of P. infestans 20 tubers per treatment were used in five independent replicates.…”
Section: Phytopathological Assaysmentioning
confidence: 99%
“…Since phytoalexin accumulation is part of the general defence response of potato tubers against P. infestans (Andreu et al 2001), and their accumulation was also reported in tubers after treatment with the plant activator β-aminobutyric acid (BABA) (Olivieri et al 2009), phytoalexin content and the expression of different enzymes that could participate in the defence mechanism were measured. Taking into account that treatment with Phi produced changes in yield related parameters, like darker green colour in leaves and a delay in crop senescence, we also analyzed the effects of foliar treatment on crop yield.…”
mentioning
confidence: 99%
“…to apply non-toxic compounds or organisms that stimulate or prime plant defence. Among the most reported effective inducing agents in potato is BABA (DL-β-aminobutyric acid), a non-protein amino acid (Cohen and Gisi 1994;Jakab et al 2001;Cohen 2002;Kim and Jeun 2007;Altamiranda et al 2008;Olivieri et al 2009). Only once has it been reported to have effect also under field conditions and this study was carried out in Israel (Cohen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…the level of resistance (Andreu et al 2006;Altamiranda et al 2008 andOlivieri et al 2009). Altamiranda et al (2008) reported that foliar treatments with BABA 30 days after crop emergence showed a 60% and 20% efficacy against late blight in the moderately resistant cv.…”
Section: Introductionmentioning
confidence: 99%
“…incognita and M. chitwoodi (Ge et al, 1999;Nandi et al, 2003;Altamiranda et al, 2008;Olivieri et al, 2009;dos Santos et al, 2013;Moahmed et al, 2013). However, there are hardly any studies investigating the effect of BABA against complexes of these phytopathogens.…”
Section: Discussionmentioning
confidence: 99%